PENGARUH PENGGUNAAN FREKUENSI GELOMBANG BUNYI TERHADAP PERTUMBUHAN BENIH JAGUNG (Zea mays) DAN KACANG HIJAU (Vigna radiate) - Rahmaniah Rahmaniah; Nurjannah Nurjannah; Muh. Said L (Teknosains, 2017)
The research was conducted to determine the influence ofusage frequency sound waves to grow seed corn and green beans. Themethod used in this study that the samples are given three types oftreatment with the sound source given to this type of audiosonicfrequency, ultrasonic and natural conditions. The results showed thatthe samples give growth response (height parameter of the plant, leafwidth, leaf number and leaf length) are good as the samples treatedwith ultrasonic frequency of administration.